Characterization of GABAB-receptor mediated neurotransmission in the human cortex by paired-pulse TMS–EEG - Premoli, Isabella; Rivolta, Davide; Espenhahn, Svenja; Castellanos, Nazareth; Belardinelli, Paolo; Ziemann, Ulf; Müller-Dahlhaus, Florian (NeuroImage (Orlando, Fla.), 2014)
GABAB-receptor (GABABR) mediated inhibition is important in regulating neuronal excitability. The paired-pulse transcranial magnetic stimulation (TMS) protocol of long-interval intracortical inhibition (LICI) likely reflects this GABABergic inhibition. However, this view is based on indirect evidence from electromyographic (EMG) studies. Here we combined paired-pulse TMS with simultaneous electroencephalography (paired-pulse TMS–EEG) and pharmacology to directly investigate mechanisms of LICI at the cortical level. We tested the effects of a conditioning stimulus (CS100) applied 100ms prior to a test stimulus (TS) over primary motor cortex on TS-evoked EEG-potentials (TEPs). Healthy subjects were given a single oral dose of baclofen, a GABABR agonist, or diazepam, a positive modulator at GABAARs, in a placebo-controlled, pseudo-randomized double-blinded crossover study. LICI was quantified as the difference between paired-pulse TEPs (corrected for long-lasting EEG responses by the conditioning pulse) minus single-pulse TEPs. LICI at baseline (i.e. pre-drug intake) was characterized by decreased P25, N45, N100 and P180 and increased P70 TEP components. Baclofen resulted in a trend towards the enhancement of LICI of the N45 and N100, and significantly enhanced LICI of the P180. In contrast, diazepam consistently suppressed LICI of late potentials (i.e. N100, P180), without having an effect on LICI of earlier (i.e. P25, N45 and P70) potentials. These findings demonstrate for the first time directly at the system level of the human cortex that GABABR-mediated cortical inhibition contributes to LICI, while GABAAR-mediated inhibition occludes LICI. Paired-pulse TMS–EEG allows investigating cortical GABABR-mediated inhibition more directly and specifically than hitherto possible, and may thus inform on network abnormalities caused by disordered inhibition, e.g. in patients with schizophrenia or epilepsy.